Investigations of Accelerated Climate Aged Wood Substrates by Fourier Transform Infrared Material Characterization - Bjørn Petter Jelle; Petra Rüther; Per Jostein Hovde (Advances in Materials Science and Engineering)
Fourier transform infrared (FTIR) material characterization by applying the attenuated total reflectance (ATR) experimental technique represents a powerful measurement tool. The ATR technique may be applied on both solid state materials, liquids and gases with none or only minor sample preparations, also including materials which are nontransparent to infrared radiation. This facilitation is made possible by pressing the sample directly onto various crystals, for example, diamond, with high refractive indices, in a special reflectance setup. Materials undergoing ageing processes by natural and accelerated climate exposure, decomposition and formation of chemical bonds and products, may be studied in an ATR-FTIR analysis. In this work, the ATR-FTIR technique is utilized to detect changes in selected wood building material substrates subjected to accelerated climate exposure conditions. Changes in specific FTIR absorbance peaks are designated to different wood deterioration processes. One aim is by ATR-FTIR analysis to be able to quantitatively determine the length of the wood ageing time before priming/treatment. Climate parameters like temperature (including freezing/thawing), relative air humidity, wind driven rain amount, solar and/or ultraviolet radiation, and exposure duration may be controlled in different climate ageing apparatuses. Both impregnated and raw wood samples have been employed in the experimental investigations.